PERCEPTIONS OF CONSUMERS TOWARDS PATANJALI PRODUCTS AT HYDERABAD METRO CITY- AN EMPIRICAL STUDY - Gardasu, Sathyanarayana; Saxena, Ramesh Raj (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the perceptions of consumers towards Patanjali products at Hyderabad metro city. The objective of the study is to explore the perceptions formed among the consumers. The study methodology is based on the survey conducted among a cross sectional consumer segments. The primary data is collected from the respondents. The entire data was utilized for a well-structured survey/questionnaire. Researcher was applied well know statistical methods in this study such as Descriptive and inferential statistics are used to investigate the basic/primary data and underlying assumptions. Analysis provides insights into consumer behavior and on the perceptions formed towards Patanjali products such as natural, ayurbenefits quality and low price. This study concludes that there is enough evidence of satisfaction among consumers.